Association between SQSTM1 dysregulation and risk in alopecia areata: a Mendelian randomization study - Hu, Lifang; Wan, Sheng; Song, Xiuzu (Frontiers in Immunology, 2025)
BackgroundAlopecia areata (AA) is an autoimmune disease typified by nonscarring hair loss. It manifests as a heterogeneous disorder with diverse clinical presentations and variable treatment responses, underscoring the significance of identifying novel biomarkers for precision management.ObjectiveThis study aims to explore the relationship between metabolic reprogramming-related genes (MRRGs) and the risk of developing AA.MethodsMRRGs were identified through the GeneCards database and existing literature. Genetic instruments were obtained from the eQTLGen database, and AA-related data were retrieved from the OpenGWAS database. The TwoSampleMR R package was applied for statistical analysis. Additionally, RT-qPCR and immunofluorescence assays were performed to validate the expression of target genes in AA-affected hair follicles and healthy controls.ResultsSix MRRGs (DLD, NFE2L2, SDHB, SLC2A1, PSAT1, and SQSTM1) showed significant causal associations with AA. RT-qPCR analysis revealed markedly elevated SQSTM1 mRNA levels in AA-affected hair follicles compared with healthy controls. Immunofluorescence confirmed increased SQSTM1 protein accumulation alongside reduced LC3B-II expression in AA-affected hair follicles.ConclusionsThis study underscores the significant association between SQSTM1 and AA, advancing our understanding of AA pathophysiology.